DIETA CETOGÊNICA INDUZ ALTERAÇÕES METABÓLICAS E HEPÁTICAS EM ANIMAIS OBESOS - CARVALHO, Suena Cristina Rodrigues de (2022)
Background: Obesity is a metabolic disorder with increasing prevalence at a global level, becoming one of the biggest public health problems today. In this context, nutritional interventions aimed at controlling this disease assume an important relevance. The ketogenic diet (KD) is a diet composed of high levels of fat and low carbohydrates and referred to as efficient for rapid weight loss. Despite its wide use, the effects of this diet on metabolism and liver function are still controversial. Objective: To evaluate the subchronic effects of the ketogenic diet (KD) on the general metabolism and liver function of mice with obesity and other metabolic disorders. Methods: Swiss male mice after weaning were divided into two groups: obese group that received cafeteria diet (CAF) and control group (CTR) that received standard diet. After 12 weeks of follow-up, the animals were divided into 5 groups: CTR/CTR group, which continued receiving CTR chow; CTR/DC group, which replaced the CTR diet with DC; CAF/CAF group, which continued with the diet cafeteria; CAF/CTR group, which replaced the CAF diet with CTR; and CAF/DC group, which replaced the CAF ration with DC. The groups were followed for an additional 8 weeks. During the entire experimental period, measurements of body weight, food intake, glycemic and lipid levels, evaluation of transaminases, degree of glucose tolerance and insulin resistance were performed. After euthanasia, blood was collected for final biochemical and insulin and liver measurements to evaluate oxidative stress and histopathological profile. Results: The CAF diet (CAF/CAF group) was efficient in inducing an obesogenic profile marked by central obesity, dyslipidemia, hyperglycemia, glucose intolerance, insulin resistance, liver damage, oxidative stress and hepatic steatosis. And the administration of DC to previously obese animals (CAF/DC group) was not able to change this dysfunctional profile, being able to control only glycemic levels. Likewise, the administration of DC diet to control animals (CTR/DC group) also led to the establishment of metabolic and hepatic disorders, such as the mentioned groups above. On the other hand, replacing the CAF diet with CTR (CAF/CTR group) was efficient in reversing all these parameters. Conclusion: Our dataset suggests that CD intervention does not lead to weight loss, it establishes metabolic dysfunctions in healthy individuals and worsens it in obese individuals and leads to the development of non-alcoholic fatty liver disease. Replacing a hypercaloric diet with a normocaloric one is more effective in controlling metabolic disorders.